Effect of Water on a Hydrophobic Deep Eutectic Solvent - Kivelä, Henri; Salomäki, Mikko; Vainikka, Petteri; Mäkilä, Ermei; Poletti, Fabrizio; Ruggeri, Stefano; Terzi, Fabio; Lukkari, Jukka (The journal of physical chemistry. B, 2022)
Deep eutectic solvents (DESs) formed by hydrogen bond donors and acceptors are a promising new class of solvents. Both hydrophilic and hydrophobic binary DESs readily absorb water, making them ternary mixtures, and a small water content is always inevitable under ambient conditions. We present a thorough study of a typical hydrophobic DES formed by a 1:2 mole ratio of tetrabutyl ammonium chloride and decanoic acid, focusing on the effects of a low water content caused by absorbed water vapor, using multinuclear NMR techniques, molecular modeling, and several other physicochemical techniques. Already very low water contents cause dynamic nanoscale phase segregation, reduce solvent viscosity and fragility, increase self-diffusion coefficients and conductivity, and enhance local dynamics. Water interferes with the hydrogen-bonding network between the chloride ions and carboxylic acid groups by solvating them, which enhances carboxylic acid self-correlation and ion pair formation between tetrabutyl ammonium and chloride. Simulations show that the component molar ratio can be varied, with an effect on the internal structure. The water-induced changes in the physical properties are beneficial for most prospective applications but water creates an acidic aqueous nanophase with a high halide ion concentration, which may have chemically adverse effects.